2001
DOI: 10.1557/proc-691-g6.5
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Lateral Momentum in Heterostructure Integrated Thermionic Coolers

Abstract: Thin film thermionic coolers use selective emission of hot electrons over a heterostructure barrier layer from emitter to collector resulting in evaporative cooling. In this paper a detailed theory of electron transport perpendicular to the multilayer superlattice structures is presented. Using Fermi-Dirac statistics, density-of-states for a finite quantum well and the quantum mechanical reflection coefficient, the currentvoltage characteristics and the cooling power density are calculated. The resulting equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This structure is intentionally chosen to compare the model presented here with previous results on thermionic cooling performance. [30][31][32] It has been shown that the figure-of-merit for thermionic cooling is about half of that of thermoelectric cooling in InGaAs. In Fig.…”
Section: Ingaas Based Superlatticesmentioning
confidence: 99%
“…This structure is intentionally chosen to compare the model presented here with previous results on thermionic cooling performance. [30][31][32] It has been shown that the figure-of-merit for thermionic cooling is about half of that of thermoelectric cooling in InGaAs. In Fig.…”
Section: Ingaas Based Superlatticesmentioning
confidence: 99%
“…Two cases of electron transports in the superlattice are considered: when transverse momentum during thermionic emission is conserved and when transverse momentum is not conserved. [10][11][12][13] The plot shows that, in both cases, superlattice transport does not improve much the ZT over the bulk values. 14 Basically, this is due to the small conduction band offset of the SiGe/ Si superlattice, which is about 12% ͑E b ϳ 23 meV for the proposed structure͒.…”
Section: N-type Sige/si Superlattice Power Generatormentioning
confidence: 95%
“…One can describe the effect of potential barriers as a mean to increase the thermoelectric power factor (the square of the Seebeck coefficient times the electrical conductivity). The fact that there is a trade-off between electrical conductivity and the Seebeck coefficient and that we can not keep increasing the number of free carriers and get higher and higher power factors is an intriguing effect which has not been discussed in detail from a fundamental point of view 18,19,20 . One way to look at this problem, is to consider the differential conductivity of electrons in typical semiconductors and metals.…”
Section: Single and Multibarrier Thermionic Devicesmentioning
confidence: 99%
“…volume V 1 in Fig. 2(b)) 16,17,19,31,32 . There are many hot electrons that have large transverse momentum.…”
Section: Conservation Of Tramsverse Momentum In Thermionic Emissionmentioning
confidence: 99%